Gun Violence and U.S. Obligations under the Inter- American System for the Protection of Human Rights - Christina M. Cerna (Washington University Journal of Law & Policy, 2019)
This article discusses the human rights aspects of gun violence from the perspective of the Organization of American States. The article explains the history, structure, and procedure of the OAS body that is charged with reviewing allegations of deprivations of human rights. Because exhaustion of claims at the national level is not required when the national law does not recognize a certain claim, the article argues that American victims of gun violence should be able to proceed directly to the international tribunal. In order for this to occur, the U.S. would need to ratify a treaty assenting to such jurisdiction; the article argues in favor of this outcome.
Keywords: human rights; gun violence; Inter-American System for the Protection of Human Rights; Organization of American States